PROFESSIONAL COMMITMENT OF FRONTIER REGION TEACHERS: A REVIEW OF THEORY OF PLANNED BEHAVIOR (STUDY IN THE BORDER REGION OF SAMBAS-SARAWAK REGENCY, MALAYSIA) - Amrazi Zakso (Jurnal Scientia, 2023)
This study examines the effect of variables on gender, employment status, school level, teacher tenure, school climate, and teacher professional attitudes. Data were obtained from a sample of 138 border region teachers, who were asked to fill out the questionnaire provided and analyzed using the stepwise multiple regression method. The results show that the professional commitment of teachers in border areas is still relatively low. This low professional commitment is significantly influenced by the school climate, the professional attitude of the teacher, and the level of the school where the teacher teaches. The level of the school where the teacher teaches has a significant direct effect on both the school climate and the attitude of the teacher to his profession. The professional commitment of teachers in elementary schools is actually higher than the professional commitment of middle school and high school/vocational school teachers. The results of this study recommend that the development of teachers in border areas, apart from focusing on professional development, also needs to be directed at increasing their professional commitment through continuous coaching by both school supervisors and local governments in accordance with their respective authorities.